Everything will be okay : life lessons for young women (from a former young woman) - Perino, Dana (Twelve, 2021)
The Fox News co-host draws on her personal boundary-breaking experiences to counsel young women on how to find inspiration and motivation, reframe their thinking, believe in themselves, and understand their power.